Challenges Facing CRISPR/Cas9-Based Genome Editing in Plants - Son, Seungmin; Park, Sang Ryeol (Frontiers in Plant Science, 2022)
The development of plant varieties with desired traits is imperative to ensure future food security. The revolution of genome editing technologies based on the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated nuclease 9 (Cas9) system has ushered in a new era in plant breeding. Cas9 and the single guide RNA (sgRNA) form an effective targeting complex on a locus or loci of interest, enabling genome editing in all plants with high accuracy and efficiency. Therefore, CRISPR/Cas9 can save both time and labor relative to what is typically associated with traditional breeding methods. However, despite improvements in gene editing, several challenges remain that limit the application of CRISPR/Cas9-based genome editing in plants. Here, we focus on four issues relevant to plant genome editing: 1) plant organelle genome editing; 2) transgene-free genome editing; 3) virus-induced genome editing; and 4) editing of recalcitrant elite crop inbred lines. This review provides an up-to-date summary on the state of CRISPR/Cas9-mediated genome editing in plants that will push this technique forward.